Tingkat Adopsi Petani Pada Penggunaan Teknologi Biofarm Studi Kasus Petani Padi Organik GAPOKTAN Sulek Raya Kabupaten Bondowoso - Suryandari, Ayu; Mazwan, M. Zul (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Oranic rice farming in indonesia is experiencing rapid development due to increasing public awareness of health concerns, yet faces various constraints such as limited availability of organic fertilizers and biopesticides. This study aims to evaluate farmers’ adaption levels of biofarm technology as a solution in organic rice farming. The research employed a quantitative approach by distributing offline questionnaires to 30 members of GAPOKTAN Sulek Raya in Bondowoso. Regency who participated in the biofarm technology pilot project. Sampling was conducted using purposive sampling technique and data were analyzed using structural equation modeling-partial least square (SEM-PLS). Results showed that mentoring effectiveness (X1) positvely influenced the level of biofarm tecnology adoption with a path coefficient of 0,51, while farmes’ technological readiness (X2) had no significant effect and teknological advancement (X3) has a significant influence with a path coefficient of 0,38. Overall, the three independent variabels explained 43% of the variation in farmers’ innovation adoption levels regarding biofarm technology. This research recommends the importance of farmers’ consistency in using biofarm tecnology to overcome fertilizer and biopesticide scarcity, as well as government support through policies and incentives for organic rice rafmers.